2015
DOI: 10.1007/s40615-015-0167-y
|View full text |Cite
|
Sign up to set email alerts
|

How Does Managed Care Improve the Quality of Breast Cancer Care Among Medicare-Insured Minority Women?

Abstract: Compared to Medicare fee-for-service, ethnic and racial disparities among Medicare Advantage users were reduced. We observed fewer disparities, but not an elimination of disparities, among Medicare Advantage enrollees receiving breast cancer care with an organizational and patient component of care. This suggests managed care may still need to focus on minority patient empowerment and involvement in care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…A similar study reported that ethnic minorities in European countries reported less satisfaction with health care than native majority patients that their health care was also disadvantaged, thus revealing diminished quality of care to minority patients (Hanssens, Detollenaere, Hardyns, & Willems, 2016). A secondary analysis study in the United States with a large dataset suggested that patient-centered care and managed care for ethnic minority patients may reduce medical disadvantages and increase quality of care to those populations (Smith-Gagen, Loux, Drake, & Pérez-Stable, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…A similar study reported that ethnic minorities in European countries reported less satisfaction with health care than native majority patients that their health care was also disadvantaged, thus revealing diminished quality of care to minority patients (Hanssens, Detollenaere, Hardyns, & Willems, 2016). A secondary analysis study in the United States with a large dataset suggested that patient-centered care and managed care for ethnic minority patients may reduce medical disadvantages and increase quality of care to those populations (Smith-Gagen, Loux, Drake, & Pérez-Stable, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Health outcomes for special populations are improved when management is modified to fit their specific needs. This finding has been duplicated in disabled (Burns, 2009;Hall, Kurth, & Chapman, 2015), homeless (Levitt et al, 2013;McCormack, Hoffman, Wall, & Goldfrank, 2013;Patterson, Nochajski, & Wu, 2014), minority (Eberly, Davidoff, & Miller, 2010;Smith-Gagen, Loux, Drake, & Perez-Stable, 2016), female (Bierman & Clancy, 2000;Kneipp et al, 2013), pediatric (Morris, Schettine, Roohan, & Gesten, 2011), elderly (Ahmed, Taylor, McDaniel, & Dyer, 2012;Black, 2011;Kwak, Kramer, Lang, & Ledger, 2013), and hospice (Brink & Smith, 2008) populations.…”
Section: Interpretation Of the Review Resultsmentioning
confidence: 94%